Through Thick and Thin: Changes in Creativity During the First Lockdown of the COVID-19 Pandemic - Lopez-Persem, Alizée; Bieth, Théophile; Guiet, Stella; Ovando-Tellez, Marcela; Volle, Emmanuelle (Frontiers in Psychology, 2022)
COVID-19 took us by surprise. We all had to face the lockdown and pandemic that put us in a new context, changing our way of life, work conditions, and habits. Coping with such an unprecedented situation may have stimulated creativity. However, the situation also restricted our liberties and triggered health or psychological difficulties. We carried out an online survey (n=380) to examine whether and how the COVID-19 related first lockdown period was associated with creativity changes in France. Despite a global negative subjective experience of the situation, participants reported that they were more creative during the lockdown than before. Positive changes were linked with more time availability, more motivation, or the need to solve a problem while negative changes were related to negative affective feelings or a lack of resources or opportunities. This study documents the effects of the first lockdown period on creativity and the factors that influenced it.